2020
DOI: 10.7202/1070245ar
|View full text |Cite
|
Sign up to set email alerts
|

Enjeux et solutions en santé mentale et travail : le point de vue des gestionnaires d’une grande organisation de santé

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne. https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit.Érudit est un consortium interuniversitaire sans but lucratif composé de l'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 39 publications
(25 reference statements)
2
25
0
Order By: Relevance
“…The feeling of work overload, considered an important organizational constraint in this study, has also been reported in other studies focusing on managers in public sector (e.g. Asplund et al, 2022;Bj€ orklund et al, 2013;Bolduc and Baril-Gingras, 2010;Corbi ere et al, 2020;Dellve and Wikstr€ om, 2009;Gilbert et al, 2019;Wallin et al, 2014). Corbi ere et al (2020) mentioned that this work overload could be a significant obstacle for managers who have to do proximity management with their employees.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The feeling of work overload, considered an important organizational constraint in this study, has also been reported in other studies focusing on managers in public sector (e.g. Asplund et al, 2022;Bj€ orklund et al, 2013;Bolduc and Baril-Gingras, 2010;Corbi ere et al, 2020;Dellve and Wikstr€ om, 2009;Gilbert et al, 2019;Wallin et al, 2014). Corbi ere et al (2020) mentioned that this work overload could be a significant obstacle for managers who have to do proximity management with their employees.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to navigating ambiguous roles, they also face conflicting demands (Asplund et al, 2022;Tessier, 2006;Udod et al, 2017) and ethical dilemmas (Dellve and Wikstr€ om, 2009). These restrictions lead to difficulty fulfilling their roles with employees (Corbi ere et al, 2020;Gilbert et al, 2019). Knies et al (2017) also highlighted the difficulties encountered by managers in the public sector in exercising their autonomy, where there are multiple rules and procedures imposed by the government and the prevalence of "red tape," defined as "rules, regulations, and procedures that remain in force and entail a compliance burden for the organization but have no efficacy for the rules' functional object" (Bozeman, 1993;Rainey et al, 1995).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations